The judicial imagination writing after Nuremberg - Stonebridge, Lyndsey 1965- (Edinburgh University Press, 2011)
Tells the story of the struggle to imagine new forms of justice after Nuremberg
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: West, Rebecca / 1892-1983; Arendt, Hannah / 1906-1975; Spark, Muriel; Bowen, Elizabeth / 1899-1973; Murdoch, Iris; Arendt, Hannah -- 1906-1975; West, Rebecca -- 1892-1983; Spark, Muriel -- 1918-2006; Murdoch, Iris -- 1919-1999; Bowen, Elizabeth -- 1899-1973; Geschichte 1900-2000; Geschichte; Justice in literature; Law and literature / History / 20th century; English literature / 20th century / History and criticism; Literatur; Nürnberger Prozesse; Englisch; Gerechtigkeit -- Motiv